Response Surface Optımızatıon Of Clove Oıl Extractıon - Bazil Wilfred C., S. Elizabeth Amudhini Stephen, D. Sriram (International Journal of Advanced Science and Technology, 2020)
Clove oil is one the abundantly used aromatic compound in various industries. It has numerous essential oils in them. Among which about 70% is of it is eugenol. Eugenol is has a wide range of applications in cosmetics and pharmaceutical industries. In general eugenol extracted is done by various methods such as Steam Distillation, Maceration, Cold Press Extraction, Solvent Extraction, etc. Here in this paper the extraction is done with the supercritical carbon dioxide as the solvent. The temperature and pressure were taken as the independent variables. Varying these two independent variables the optimum condition for the extraction of eugenol was determined. The mathematical modelling for the optimization of this extraction process was done with the design expert software in Response Surface Methodology. For which the optimum extraction temperature and pressure were found to be 308.649K and 12.5485 MPa